2017
DOI: 10.24969/hvt.2017.18
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian vein diameters measured by MDCT in women without evidence of pelvic congestion syndrome

Abstract: Abstract:Objectives: The purpose of this study was to clarify reference values for ovarian veins diameters in women without evidence of primary or secondary pelvic venous insufficiency and to determine factors influencing these parameters. Methods: Multidetector computed tomography images and medical records of 197 women were retrospectively reviewed. The patients' age, body mass index and history of parturition were examined. Results: Diameters of right ovarian veins (ROV) and left ovarian veins (LOV) ranged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…In current study, our findings (mean right and left ovarian venous diameter, 3.66 mm and 4.20 mm, respectively) fall in range with previous study-findings. We found relatively higher diameters in left ovarian veins similar to some previous studies [9,19] which was found to be statisti-cally significant (P<0.05). It could be due to natural anatomical factors which make the left gonadal vein more vulnerable to congestion and dilatation [2].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In current study, our findings (mean right and left ovarian venous diameter, 3.66 mm and 4.20 mm, respectively) fall in range with previous study-findings. We found relatively higher diameters in left ovarian veins similar to some previous studies [9,19] which was found to be statisti-cally significant (P<0.05). It could be due to natural anatomical factors which make the left gonadal vein more vulnerable to congestion and dilatation [2].…”
Section: Discussionsupporting
confidence: 91%
“…In a study by Pavkov et al [20] on plastinated cadavers, the mean diameter of ovarian veins was 3.49 mm; in our study it was 3.93 mm. A multi-detector computed tomography based study [9] showed the mean right and left ovarian venous diameters as 2.9 and 3.2 mm, respectively. Another CT based study by Nascimento et al [18] showed the average diameters were 4.4 mm and 4.5-6.5 mm in right and left ovarian veins, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the left, the ovarian vein flows into the left renal vein; on the right, however, the ovarian vein flows directly into the inferior vena cava. All pelvic venous plexuses anastomose with one other, and these anastomoses vary considerably in their flow capacity 22 . A number of studies have reported the significance of anatomy in PVI, which occurs frequently in the left ovarian vein 23 .…”
Section: Discussionmentioning
confidence: 99%